Global Citizenship Education in Action: Students’ Reflections and Their Impact on a Local College’s Core Values - Ronald A. Gonzales; Roseller H. Rizal; Gerby R. Muya; Simplicio P. Alba; Mary Rose F. Montano; Renante A. Artificio (Inclusive Society and Sustainability Studies, 2026)
Despite the growing integration of global citizenship education (GCED) in higher education institutions globally and locally, limited empirical evidence exists on how such programs tangibly influence students' values and perspectives—particularly from the students' standpoint. Thus, this study examines how the reflections of the City College of Calamba's students who have completed the GCED course align with the core values of social responsibility, national service, moral uprightness, and commitment to lifelong learning. Specifically, it aims to examine how student reflections vary across demographic groups, investigate the correlation between students’ reflections on the GCED course and their perceptions of the course content and delivery, and identify which aspects of the GCED course students find most influential in shaping their values and outlook as future global professionals. Using a descriptive-correlational research design, the researchers purposively selected 308 City College of Calamba (CCC) students who had completed the Global Citizenship Education (GCED) course during the first semester of AY 2024-2025. Data drawn were analyzed using mean, standard deviation, the Kruskal-Wallis test, and Spearman’s rho. Results revealed that students have generally developed strong reflections on Global Citizenship Education (GCED), particularly in social responsibility (r = .770), national service (r = .754), moral uprightness (r = .776), and commitment to lifelong learning (r = .741). However, significant differences in reflections emerged by academic program and by the semester or year in which the course was taken, suggesting that pedagogical strategies, course delivery formats, and contextual influences affect how students internalize GCED values. The study proposed an action plan that includes capacity building for faculty in reflective and contextualized pedagogies and embedding GCED themes.